CASE OF TREATMENT OF UNRESECTABLE HEPATOCELLULAR CARCINOMA OF THE LIVER THROUGH THE HEPATIC ARTERY CHEMOEMBOLIZATION M - A. I. Gritsaenko; I. F. Mukhamedyanov; V. V. Pogadaev; R. R. Ishtukov (Креативная хирургия и онкология, 2017)
In the article the method of treatment of unresectable hepatocellular carcinoma has shown. The method is based on the tumor vessels chemoembolization saturating areas with Doksirubitsin mkr Terumo Biocompatibles DCBead 100-300. This technique allows to stop further spread of tumor and to achieve the regress.